2015
DOI: 10.1002/ejic.201402970
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Different Isomers of Phosphine–Imidazolyl and –Pyridyl Ruthenium(II) Complexes Affecting the Catalyst Activity in the Acceptorless Dehydrogenation of Alcohols

Abstract: The synthesis, reactivity, and catalytic activity of Ru II complexes with different pyridine-and imidazole-based P,N ligands are reported. The investigations reveal a strong influence of the N-heterocycle and the steric demand of the phosphine groups on the stability of different isomers of [L 2 RuX 2 ] (L = P,N ligand; X = Cl, H). The imidazole-based complex 5 with dicyclohexylphosphine groups was found to be the most active precatalyst for the acceptorless dehydrogenation of primary alcohols, whereas differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
0
14
1
1
Order By: Relevance
“…Thus, it is not surprising that we were able to isolate two of these isomers (3c I and 3c II ). Whereas Langer et al [12] reported these three isomers with a similar P,N-bidentate ligand, in our study of the coordination behavior of 1c towards Ru(II) we found the initial formation of 3c I (as a kinetic product) which slowly isomerizes into a mixture of 3c I and 3c II , where 3c II could be separated by crystallization. There were no spectroscopic hints at the formation of the N-trans isomer 3 V .…”
Section: Ruthenium(ii) Bis-chelatescontrasting
confidence: 58%
See 4 more Smart Citations
“…Thus, it is not surprising that we were able to isolate two of these isomers (3c I and 3c II ). Whereas Langer et al [12] reported these three isomers with a similar P,N-bidentate ligand, in our study of the coordination behavior of 1c towards Ru(II) we found the initial formation of 3c I (as a kinetic product) which slowly isomerizes into a mixture of 3c I and 3c II , where 3c II could be separated by crystallization. There were no spectroscopic hints at the formation of the N-trans isomer 3 V .…”
Section: Ruthenium(ii) Bis-chelatescontrasting
confidence: 58%
“…Tables: Table 1 Selected bond lengths (Å) and angles (°) of 1a, 1b and 1c. (10) 96.73 (13) 103.26 (12) 97.13 (11) 104.31 (12) 102.05 (10) 103.21(10) C-P2-N2 99.33 (12) 104.97 (11) 102.76 (9) 103.72(10) P-N-C carbonyl 115.81 (15) 117.69 (19) 115.08 (17) 117.86 (14) 116.17 (17) Selected bond lengths (Å) and angles (°) of 3c I and 3c II . …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations